Transvaginal Drainage of Pelvic Fluid Collections Unsuitable for Transabdominal Approach - Hwa Jin Lee; Ji Hoon Shin; Gun Ha Kim; Heung Kyu Ko (Journal of the Korean Society of Radiology)
Purpose To evaluate the efficacy and safety of ultrasonography- and fluoroscopy-guided transvaginal catheter drainage for pelvic fluid collection. Materials and Methods This single-center retrospective study included nine female patients who underwent transvaginal drainage for pelvic fluid collection unsuitable for transabdominal access between October 2016 and January 2023. The study analyzed patient symptoms and signs, ultrasonography and CT findings, transvaginal approach details, and technical and clinical outcomes, including complications. Catheters of size 7 or 8.5-Fr, with or without an endocavitary needle guide were used for the puncture. Results Pelvic fluid collections were primarily post-operative (n = 7) or from patients with primary tubo-ovarian abscesses (n = 2). All patients achieved technical success, defined as the successful insertion of the drainage catheter at the site of target fluid collection, and clinical success, defined as the improvement of symptoms with catheter removal within 1 week. In seven cases, the procedure was assisted by an endocavitary needle guide. The median catheter indwelling period was 2 days, with two minor complications: accidental catheter removal and urinary bladder puncture, both of which were managed without further complications. Conclusion Ultrasonography- and fluoroscopy-guided transvaginal drainage are effective and safe methods for managing pelvic fluid collections that are unsuitable for a transabdominal approach.